KONFLIK BATIN TOKOH-TOKOH DALAM NOVEL CHEER DANSHI!! KARYA ASAI RYO - Restiti, Ni Putu Yuley (Humanis, 2016)
This thesis entitled internal conflict of the characters in the novel Cheer Danshi!! by Asai Ryo. The purposes of this study are to know internal conflict experienced  by characters and to know internal conflict solution of the characters in the novel Cheer Danshi!! by Asai Ryo. This research used descriptive analysis and informal methods as methods. The theories used in this study are psychological theory of literature and theory of Erik Erikson’s psychosocial. Based on the analysis, this research results are seen through psychosocial theory, characters in the novel Cheer Danshi!! by Asai Ryo experience internal conflict caused by four problems, namely: 1) family, 2) social life, 3) self confidence, 4) friendship interaction. Meanwhile, the problems of internal conflict based on the identity crisis of each character can be resolve by the formation of the cheerleading squad. In this study, a team of cheerleaders is exactly into the place of the characters in their process of self discovery.
Keywords: psychology literature, internal conflict, identity crisis